2019
DOI: 10.1071/fp18259
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the heat shock response in Arabidopsis by heat shock protein 70 inhibitor VER-155008

Abstract: The heat shock protein 90 (HSP90) inhibitor, geldanamycin, is a chemical inducer of the heat shock response (HSR) in Arabidopsis. Geldanamycin is thought to activate the heat shock signal by dissociating the HSP90-heat shock factor (HSF) complex. Recent studies have indicated that plant HSP70 is also associated with HSF, suggesting that inhibition of HSP70 may induce the HSR. However, no studies have been conducted to test this hypothesis. Here, we found that a specific HSP70 inhibitor VER-155008 activated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…These results indicated that HSP70‐16 and VDAC3 may function closely in negatively regulating seed germination under cold stress. Since HSP70‐16 is a chaperone/ATPase (Figure S2), we further examined if the inhibitory effect of HSP70‐16 on seed germination under cold stress is from its chaperone activity using a plant HSP70 ATPase activity inhibitor VER155008 (Zhang et al ., 2015; Matsuoka et al ., 2019). Neither mutant seeds ( hsp70‐16 , vdac3 and hsp70‐16vdac3 ) nor wild‐type seeds changed their earlier germination patterns under 4°C up to 196 h in the presence of VER155008 (25 μM or 50 μM) (Figure 1c), indicating that HSP70‐16 negatively regulates seed germination under cold stress in a manner that is independent of its chaperone activity.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that HSP70‐16 and VDAC3 may function closely in negatively regulating seed germination under cold stress. Since HSP70‐16 is a chaperone/ATPase (Figure S2), we further examined if the inhibitory effect of HSP70‐16 on seed germination under cold stress is from its chaperone activity using a plant HSP70 ATPase activity inhibitor VER155008 (Zhang et al ., 2015; Matsuoka et al ., 2019). Neither mutant seeds ( hsp70‐16 , vdac3 and hsp70‐16vdac3 ) nor wild‐type seeds changed their earlier germination patterns under 4°C up to 196 h in the presence of VER155008 (25 μM or 50 μM) (Figure 1c), indicating that HSP70‐16 negatively regulates seed germination under cold stress in a manner that is independent of its chaperone activity.…”
Section: Resultsmentioning
confidence: 99%
“…GDA and sanguinarine inhibited luciferase folding by wheat (Triticum aestivum L.) germ chaperones at similar efficiencies [47]. This suggests that sanguinarine induces HSR probably via the inhibition of chaperones that hold HSF [48]. However, it is unclear how essential oil HTLEs such as isothiocyanates and monoterpenes promote HSR in plants.…”
Section: Htlesmentioning
confidence: 99%